Analisis Kualitas Pelayanan, Harga, dan Promosi melalui Instagram terhadap Kepuasan Pelanggan (Studi kasus PT. XYZ Wilayah Pemasaran Purwakarta) (Current Research in Education: Conference Series Journal, 2023)
Along with the development of technology and the economy as well as increasing business competition in the global market, companies compete to be able to provide services, prices, and promotions that are more satisfying to customers and can offer competitive prices. This is done to get new customers and retain customers. One of the tea drinks produced by PT. XYZ is bottled tea, the first packaged ready-to-drink tea in Indonesia that has been developed and maintained for decades. The number of competitors makes Teh Botol Sosro remain firm in the fight in the soft drink market. The purpose of this study was to determine the effect of service quality, price and promotion variables on customer satisfaction. The method used in this research is the Systematic Literature Review (SLR) of journal papers published from 2017-2021. There are three Research Questions (RQ) set in this study. The results showed that the variables used in this research model, namely service quality, price and promotion each had a significant and positive effect on customer satisfaction for Teh Botol Sosro in the Purwakarta marketing area. These results indicate that the better the quality of service, price and promotion, the customer satisfaction will increase.